Load Characterization for Distributed Virtual Environments - Singh, Lally; Gračanin, Denis (Electronic Communications of the EASST, 2009)
Due to their sensitivity to user positions, actions, and visibility, Distributed Virtual Environments (DVEs) are well served through a focused load characterization effort. Quantified load can then be evaluated through models of the system behavior, resulting in expected behavior. A discussion of determining some characterized load from system requirements and instrumenting a DVE to provide validation metrics is also provided.